Competitive season of triathlon does not alter bone metabolism and bone mineral status in male triathletes - Maimoun, L.; Galy, O.; Coste, O.; Peruchon, E.; Micallef, J. P.; Mariano-Goulart, D.; Couret, I.; Sultan, C.; Rossi, M. (International Journal of Sports Medicine, 2004)
This longitudinal study evaluated the effects of a triathlon season on bone metabolism and hormonal status. Seven male competitive triathletes (mean age 19.3 years, range 18 - 20) with 5.0 ± 0.3 years of competition experience were tested twice during the season: at the beginning of training and 32 weeks later. Total and regional bone mineral density (BMD) was determined by dual-energy X-ray absorptiometry, while bone turnover was evaluated by specific biochemical markers: bone-specific alkaline phosphatase (B-ALP), osteocalcin, and urinary type I collagen C-telopeptide. In addition, sexual, calciotropic and somatotropic hormones were also analyzed. After 32 weeks, a BMD increase was found at the lumbar spine (1.9 %; p = 0.031) and skull (3.1 %; p = 0.048), while no variation was observed for total body or at the proximal femur. The B-ALP level decreased (-23.2 %; p = 0.031), but no variation was found for the other bone markers. 1.25 (OH)2D3, IGF-1 and the bioavailability IGF-1 index (IGF-1/IGFBP-3) increased by 18.3 % (p = 0.047), 29 % (p = 0.048), 33 % (p = 0.011), respectively, while PTH, testosterone, IGFBP-3 and cortisol concentrations were unchanged. In conclusion, the triathlon season had a moderately favourable effect on BMD, although a slowing down of bone formation activity was observed. No variation in hormonal levels was observed that could have limited the effects of exercise on bone tissue.